Severe Epididymo‐Orchitis and Encephalitis Complicating Anti‐PD‐1 Therapy. (1st April 2019) - Quach, Henry T.; Robbins, Charles J.; Balko, Justin M.; Chiu, Charles Y.; Miller, Steve; Wilson, Michael R.; Nelson, George E.; Johnson, Douglas B.
Abstract: Background: Immune checkpoint inhibitors such as pembrolizumab and nivolumab have emerged as active treatment options for patients with many cancers, including metastatic melanoma, but can also cause symptomatic or life‐threatening immune‐related adverse events, including encephalitis. Epididymitis and orchitis are rare complications of these therapies. Case Presentation: We describe herein a patient with metastatic melanoma who developed epididymo‐orchitis followed by encephalitis while receiving pembrolizumab. The patient developed testicular pain and fever after his third dose of pembrolizumab; ultrasound evaluation demonstrated bilateral epididymo‐orchitis. He then developed headaches, fever, and altered mental status over the next week and was admitted to the hospital. Lumbar puncture revealed inflammatory changes consistent with meningoencephalitis; he did not improve with broad‐spectrum antibiotics, and an extensive workup for infectious etiologies, including cerebrospinal fluid testing using a clinical metagenomic next‐generation sequencing assay, was negative. He received high‐dose steroids for suspected autoimmune encephalitis, and both his orchitis and meningoencephalitis improved rapidly after one dose. He fully recovered after a 5‐week taper of oral steroids. Discussion: Here, we report a case of epididymo‐orchitis complicating immune checkpoint inhibitor therapy. This patient subsequently developed severe encephalitis but rapidly improved with steroids. Clinicians should be aware of rare complications of these agents. Key Points: Epididymo‐orchitis is a rare and potentially life‐threatening complication of anti‐programmed death protein 1 (anti‐PD‐1) therapy. For patients on anti‐PD‐1 therapy who develop either epididymo‐orchitis or epididymitis without clear infectious cause, immune‐related adverse events should be considered in the differential diagnosis. If severe, epididymo‐orchitis related to anti‐PD‐1 therapy may be treated with high‐dose corticosteroids. Abstract : Immune checkpoint inhibitors have emerged as treatment options for patients with many cancers, but the treatment is associated with immune‐related adverse events. Epididymitis and orchitis are rare complications of these therapies. This article presents the case of a patient with metastatic melanoma who developed epididymo‐orchitis as well as encephalitis while receiving pembrolizumab.